EVALUATION OF BUREAUCRACY REFORM PROGRAM AT STATE PERSONNEL AGENCY - Ramli Effendi Idris Naibaho (IJHCM (International Journal of Human Capital Management), 2017)
The objective of this research is to evaluate the bureaucracy reform program at State Personnel Agency. The evaluation focused on five stages, namely design, installation, process, product and benefit. Qualitative approach used in this research with using Discrepansy Evaluation Model design. Data collecting with in-depth interview, orbservation and documantation study. Interview Data analyzed quantitatively through data reduction, data display, and conclussion drawing. The evaluation results toward the bureaucratic reform program at State Personnel Agency shows: (1) the program has been well defined which is indicated by an explanation of the urgency aspect, has clear goals and objectives, and equipped with key success indicator, (2) the program has been well designed including the formulation of implementation guidelines, resource preparation, work programs, and evaluation and monitoring, (3) implementation of eight areas of changes which cover organizational structuring, structuring of governance managemnt system, structuring of human resources management system, harmonization of legislation, strengthening of supervision, strengthening of performance accountability, public services, mindset and work culture is good. However, has’t shown the ideal conditions if associated with position of State Personnel Agency as a pioneer and role model for the ministries or other institutions in the implementation of bureaucratic reform program, (4) the bureaucratic reform program has given positive results in the improvement of the quality of clean bureaucracy and free of corruption, collusion and nepotism, the quality of public services, and the capacity and performance accountability, and (5) the bureaucratic reform programs can provide positive benefits in improving bureaucratic governance, enhance the positive image and improve the apparatus job performance. Therefore, State Personnel Agency needed to improve the implementation of bureaucracy reform program continuously in order to achieved the optimal resultsKeywords: Program Evaluation, And Bureaucracy Reform, Discrepancies Evaluation Model